Os direitos políticos nas constituições dos países do mercosul à luz do direito internacional dos direitos humanos - Piacentin, Antonio Isidoro (2006)
The work is presented hás as main focus the analysis of the Politics Rights in the Constitutions of the countries that are part of the Mercosul due to the International law of the Human Rights. The politics Rights are conquests of the people xho had demanded the right of, besides choosing its government, to intervene with the elaboration of the General Will of the State. The creation of the Rule of law propitiated the exercise of the public and individual freedom and the equality of the people as well. Even though, the law is the amanation of a general will, where people govern themselves. The Constitutionalization and internationalization of the human rights have initialized the legal national systems lapsings of guardianship and protection to the human beings. This acts have joined several politic administrations in many continents marked out with buoys in freedom and equalities, which will make them able to develop themselves and be part of democratic societies that will have added to this kind of administration. The democracy is, though, a supreme legal value, that demands a word-wide agenda. In this direction the Politics Rights became this libertarian model. Therefore, in this work the aim is to analyse the theoretical approach and analytical aspects o f the politic rights in the Constitutions of the countries that are part of the Mercosul towards to the International law of the Human Rights